Farmers' Organizations as innovation intermediaries for agroecological innovations in Burkina Faso. Issue 5 (3rd September 2022) - Iyabano, Aboubakar; Klerkx, Laurens; Faure, Guy; Toillier, Aurélie
ABSTRACT: Agroecology has been recognized as a paradigm that can offer multiple ecological and socio-economic benefits. In many developing countries, the promotion of agroecology is facilitated by intermediary organizations such as Farmers' Organizations (FOs). Detailed studies on how FOs support their farmers in the adoption of agroecology innovations are still scarce, and particularly there are limited studies on the roles of FOs in this realm in Africa. This paper addresses this gap by presenting a study on how FOs stimulate farmers' adoption of agroecological innovations in Burkina Faso. Three case studies of FOs were done to unravel the ways FOs support of farmers' adoption of agroecological innovations processes, using the lens of innovation intermediaries. The findings show that FOs fulfil both knowledge and innovation intermediation functions in the process of stimulating their farmers' adoption of agroecological innovations. By doing this, FOs act as a facilitator for the introduction and/or development of complementary agroecological innovations over longer periods of time. Future studies could look more deeply into how intermediation may contribute to broader transitions and how it connects with the political activities of FOs such as advocacy and lobbying.